Conservation Subdivision: Post-construction Phase – Urban Trees Can Reduce Household Carbon Footprint - Richard Vaughn; Mark Hostetler; Francisco Escobedo (EDIS)
During the post-construction phase, the conservation and planting of native trees in individual yards and open spaces can reduce household and neighborhood carbon footprints. This 5-page fact sheet discusses the importance of urban trees and their role in mitigating for climate change by avoiding carbon emissions and removing carbon dioxide from the atmosphere. Written by Richard Vaughn, Mark Hostetler, and Francisco Escobedo, and published by the UF Department of Wildlife Ecology and Conservation, June 2012.